Development of a flood index insurance product for Zambia - Batra, N.; Amarnath, Giriraj (International Water Management Institute, 2023)
Weather Risk Management Services Pvt Ltd (WRMS) is collaborating with the International Water Management Institute (IWMI) as part of the CGIAR Initiative on Climate Resilience (ClimBeR) to develop financial solutions for post-extreme climatic events. The focus is on creating parametric insurance solutions to aid vulnerable populations in managing and mitigating loss and damage caused by natural disasters, with a primary emphasis on floods.